Bone densitometry for technologists - Bonnick, Sydney Lou. (Springer, 2013)
As a technology, bone densitometry is really quite extraordinary. The ability to quantify the density of the bones at a variety of skeletal sites has truly revolutionized the approach to a number of diseases, the most important of which is osteoporosis. Using the information from the machines, especially dual-energy X ray absortiometry (DXA) technology, physicians can recommend and prescribe interventions that will slow bone loss and reduce the risk of disabling fractures. The remarkable advances in skeletal imaging with densitometry devices have made possible quantitative and diagnostic assessments of skeletal structure. However it is in fact the skill and concern of the technologist that enables all of this to happen.  In this updated and expanded third edition of their gold standard and highly praised Bone Densitometry for Technologists, Sydney Lou Bonnick, MD, FACP, and Lori Ann Lewis, MRT, CDT, again offer the most comprehensive review of the standards and developments in the field.  Here radiologic technologists, nurse practitioners, physician assistants, and dedicated densitometry technologists can find not only the state-of-the-art guidelines for bone density testing, but also a wide range of other topics, including several new chapters.  These include a new chapter on the performance of DXA lumbar spine, proximal femur and forearm studies; one on Using Absolute Risk to Predict Fracture Risk in Clinical Practice; and another providing examples of highly instructional DXA images in which artifacts or structural changes can be seen.  There are 2 new appendices and the other 10 appendices from the previous edition have been updated wherever necessary to reflect the most current information available.  In Appendix XII, the contents of the accompanying CD-ROM are reviewed. On this CD, readers will find the Precision Calculator Companion that was first included with the 2nd edition of Dr. Bonnick’s title, Bone Densitometry in Clinical Practice. An introduction to conventions in densitometry -- Densitometry techniques -- Skeletal anatomy in densitometry -- Performing a DXA PA lumbar spine, Proximal femur or forearm study -- Radiation safety in X-ray densitometry -- Quality control procedures -- Precision in bone densitometry -- Using absolute risk to predict fracture risk in clinical practice -- An overview of osteoporosis -- Interpretation of bone densitometry data -- Less than perfect scan images -- Pediatric densitometry -- VFA imaging, femoral morphometry and hip structural analysis -- Body composition analysis -- Appendices.